ҲƏР ҚЫЙЛЫ ОҚЫТЫЎ ТИЛЛЕРИ ШАРАЯТЫНДА МЕКТЕП МОТИВАЦИЯСЫН ҮЙРЕНИЎ МƏСЕЛЕСИ - Клычева, З.П. (FAN va JAMIYAT, 2022)
This article presents studies of school motivation in conditions with Karakalpak, Uzbek and Russian languages of instruction in the Republic of Karakalpakstan. The author reveals the motives of learning, the dynamics of school motivation, as well as the influence of the language of instruction on the process of socialization of modern students.